PENGUATAN KELEMBAGAAN PEMERINTAHAN DESA MELALUI PEMBENTUKAN, PENGGABUNGAN DAN PENGHAPUSAN DESA - Rauf, Rahyunir (UIR PRESS, 2015)
In the effort applying of autonomous concept of countryside, is hence needed by a existence strive reinforcement to countryside governance, strength of it governance of countryside relied on by a serious consideration to two element which substansial, namely; ( 1) countryside as a(n) subsistem governance; and ( 2) countryside as social subsistem